Efficacy and Tolerance of Silver Sulfadiazine in Grade II Burns - Kashif Ali, Farhat ul Ann Tayyaba2, Muhammad Ijaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the efficacy and tolerability of silver sulfadiazine in grade II burns. Study design: Cross sectional study. Place and duration of study: Department of Plastic surgery & Burn Unit, Sheikh Zayed Hospital Rahim Yar Khan during 01-09-2020 to 31-03-2021. Material and Methods: In this study the cases of both genders with age more than 12 years having grade II burn were included. Silver sulfadiazine was applied in 1% strength in the form of dressing on alternate day and was assessed for degree of healing on day 5, 10, 15 and 20 where final outcome was seen with the help of photographs and graphs and efficacy was labelled where there was more than 90% of epithelisation of the wound. The cases were also assessed subjectively regarding tolerance of the drug. Results: In this study 30 cases of grade II burn were included. The mean age of the subjects was 16.47±5.31 years and mean duration of burns was 6.79±2.73 hours. There were total 18 (60%) males and 12 (40%) females in this study. Mean percentage of burn was 23.31±7.49 percent. Efficacy of Silver sulfadiazine was noted in 19 (63.33%) of the cases. Out of 30 cases, 3 (10%) had excellent and 12 (40%) had optimal tolerance of the drug. Conclusion: SSD is efficacious and this efficacy is seen in 2/3rd cases suffering from grade II burn.